Narcissism of Executive Officer: Profit quality of Government Corporation - P. Febrina; T. Wahyudi; A. Azwardi (Финансы: теория и практика, 2019)
The study was motivated by the increasingly widespread phenomenon of narcissism of CEOs in various companies throughout the world, including Indonesia.he purpose of this study was to determine the impact of narcissism of the Chief Executive Officer on the profit quality of the company.The study was conducted on the purposive sampling of 20 state-owned companies listed on the Indonesia Stock Exchange in 2015 to 2018. The impact of narcissism of the CEO on the profit quality and the financial performance of the company was assessed.The author provided the mathematical justification of some provisions of the issue. The Modified Jones Model was used to evaluatethe company’s financial management. The data were analyzed by means of Multiple Liner Regression.The study showed that the narcissism of the CEO negatively affects the financial results of the company and leads to lower profits. This is consistent with the Upper Enchelons Theory, which states that the organization is a reflection of the values of its leader.